CONDITION AND STRUCTURAL ORGANIZATION OF THE GLANDULAR AREA MUCOUS MEMBDANE OF ALBINO RAT HARD PALATE UNDER THE 30-DAY-LONG EFFECT OF ACRYLIC MONOMER - Khilinich, Ye.S.; Starchenko, І.І.; Davydenko, V.Yu.; Nidzelskiy, M.Ya.; Davydenko, G.М. (World of Medicine and Biology, 2020)
Currently, the problem of the impact of removable laminar denture frames, including residual monomer, on the condition of the minor salivary glands, which play an important role in maintaining the balance in the oral cavity, remains poorly understood. Therefore, the paper was aimed at the experimental study of the effect of the monomer of the base acrylic resin “Ftoraks” on the condition and structural organization of the salivary glands of hard palate of albino rats. The findings of the study show that the monomer disrupts homeostasis of the oral cavity and causes irritation of the mucous membrane, manifested by dystrophy of the epithelial plate on day 30 of the experiment, as well as thickening of the corneal layer due to hypertrophy, which indicates the presence of hyperkeratosis. On day 30 of the experiment, thickening of the entire epithelial layer and the phenomena of hyper- and diskeratosis was detected in the experimental group; the phenomena of plethora, high lymphocyte, neutrophilic and eosinophilic leukocyte count were noted in the lamina propria of the mucous membrane and growing of relative amount of connective tissue can be regarded as the manifestation of a compensatory-adaptive reaction in response to the action of the monomer. 30-day-long experimental studies have shown insignificant effect of the monomer of the base acrylic resin “Ftoraks” on the cumulative size of the salivary glands in the submucous layer of the hard palate. Since the average recommended period of use of full removable laminar dentures is 3-5 years, it was considered necessary to continue the experiment and investigate the effect of the monomer of the base acrylic resin “Ftoraks” on the condition and structural organization of salivary glands of the hard palate of albino rats after 3, 6 and 9 months to further extrapolate the findings of the study to the human body.
Keywords: salivary glands; hard palate; mucous membrane; monomer of the acrylic resin